Biotope Distribution of The Common Fox in The Steppe Zone of Ukraine - Volokh, Anatolii; Волох, Анатолій Михайлович; Rozhenko, Nikolai (My University, 2024)
In the steppe zone, foxes use fields, meadows and steppe areas characterised by good visibility during daytime rest. A total of 37.8% of individuals were recorded in these areas, with the highest numbers on the coasts of the Dnipro (48.9%), Azov (43.3%) and Black (29.9%) Seas. In forested areas, foxes rested most often in deciduous (12.5%) and pine plantations (2.8%), while in field areas - in forest belts (6.7%), uncultivated fields (16.2%), and in orchards and vineyards (7.6%). However, the largest number of individuals (32.6%) was found in thickets of southern reeds (Phragmites australis) and other aquatic plants. In the Black Sea region, more than 45% of foxes spent the day in reed beds. This resulted in a high population density (26.6±1.37 individuals/10 ha or 4.4±0.18 per reed bed). The probability of encountering predators in such areas, which usually do not exceed 1-2 ha (49.4%), is very high - out of 231 surveyed sites, animals were absent only in 2. The location of foxes' dwellings, which they create to breed their young, is peculiar: the main number of dens (about 23%) was located on the forest margins, somewhat less - in the treeless valleys of small rivers, as well as on the banks of estuaries. In the Black Sea region, many burrows (18.5%) were found in floodplains of large rivers (Danube, Dniester, Southern Bug and Dnieper), and in the Azov region - on sea spits and islands (14.3%), as well as in numerous forest belts (11.5%). After the dust storms of 1969, many of these sites were covered with high earthen berms made of wind-blown black soil. This improved conditions for dens of all predatory animals, but especially for foxes. Already in the early 20th century in Ukraine, they began to avoid open steppes and fields, although they made holes in haystacks that had been stored for many years and used to feed sheep.
Keywords: vox; steppe zone; Ukraine; population; dynamics; structure; biotopes